Pleomorphic adenoma originating from submandibular salivary gland in an 8-year-old girl: A case report - Gani AN; Megat Shiraz MAR; Siti Aishah MA; Mazita A; Norazizah M; Sharifah NA (Penerbit UKM, 2007)
Pleomorphic adenoma (PA) typically presents as a benign slow growing, painless neoplasm of the parotid gland. PA arising from the submandibular gland in the paediatric age group is rare. Surgical excision is the treatment of choice. A case of PA in an 8-yearold Malay girl is presented. Clinically she presented with a painless right submandibular mass measuring 2x2cm. A diagnosis of Pleomorphic adenoma was made on Fine Needle Aspiration Cytology (FNAC). She underwent submandibulectomy uneventfully. Postoperatively after two years follow up, she is asymptomatic